Global Access to Indian Research: Indian STM Journals Online - Lalitha Kumari (Issues in Science and Technology Librarianship)
India has built up a strong research and development base in both the governmental and private sectors in all areas of science and technology. This has led to an impressive quantity of research publications. But the Indian scientific community has noted with great concern that Indian research findings, especially those reported in Indian journals, are underrepresented in the global knowledge base. This is a concern not only of India but of other developing nations as well. A global effort is underway to make scientific information affordable by bypassing the profit-making commercial scientific journal publishers. Using the Internet creates the possibility of establishing alternative models for the dissemination of information. The above problems may be addressed by facilitating free access to scientific information in electronic form to users worldwide. In India, many science, technology, and medical journals are now available online for a global audience through the initiatives of governmental and private non-profit publishers. This article outlines these international efforts briefly with a special focus on Indian initiatives. [ABSTRACT FROM AUTHOR]